Constrained by Ideology: Attitudinal Barriers to Undergraduate Research in Australian Teacher Education - Dobozy, Eva (Gale Publishing, 2011)
The ‘higher’ in higher education (HE) will need to be justified and reinstated, as the next generation of knowledge workers are educated in Australian universities. More precisely, teacher education programs will have to be at the forefront of this process. This means that there is an urgent need to shift current mindsets of a great number of teacher educators stuck in the industrial era, practising Fordist modes of ‘knowledge telling’. Are they depriving students of the capacity to think critically, solve complex problems, develop research skills and principally, denying them the ability to argue their point and make judgements on the basis of solid empirical evidence? An argument will be presented that outlines how educational socialisation chains carefully crafted in school education and continued in higher education are developing learner dependency on teachers’ knowledge telling approaches which are detrimental to prepare knowledge workers fit for purpose in a 21st century knowledge economy. There is an urgent need to break this chain and replace it with new links and elements, such as undergraduate research in teacher education, so that all learners can be better prepared for the demands of an uncertain but complex future.